Volumenmanagement bei Sepsis und septischer Schock - Kochanek, Matthias; Böll, Boris (DMW - Deutsche Medizinische Wochenschrift, 2018)
Sepsis and septic shock are common diseases with high mortality rates. Although volume therapy has been a central component of sepsis therapy for decades, the choice of optimal fluid and fluid intake is unclear. This paper summarizes findings on pathophysiology, clinical trial results, and current recommendations for optimal volume and fluid management in sepsis.
Keywords: Sepsis; Flüssigkeitsmanagement; septischer Schock; Organdysfunktion